2022
DOI: 10.1088/1748-3190/acaba2
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of a microfiber filter for domestic washing machines

Abstract: The development of enhanced processes for filtration is one solution for stopping the increasing freshwater and sea pollution caused by microplastic and microfibers. Major contributors to micro-X pollution are domestic devices such as washing machines, which also hold a high technical potential for separating problematic soils from waste water during cleaning cycles. The focus of the present paper are the biomimetic development of a novel concept for filtration and removal of particles such as microfibers in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Fi, filtrate; GR, gill raker; MF, mainstream flow. Schroeder et al (2019), Masselter et al (2023), andXu et al (2023) have applied vortical cross-step filtration to construct filters with reduced clogging for harmful algae collection, washing machines, and drip-irrigation systems, respectively. In their physical models, vortices generated in the slots between ribs served to reduce clogging by transporting particles to the margins of the slots.…”
Section: Cross-step Filtrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fi, filtrate; GR, gill raker; MF, mainstream flow. Schroeder et al (2019), Masselter et al (2023), andXu et al (2023) have applied vortical cross-step filtration to construct filters with reduced clogging for harmful algae collection, washing machines, and drip-irrigation systems, respectively. In their physical models, vortices generated in the slots between ribs served to reduce clogging by transporting particles to the margins of the slots.…”
Section: Cross-step Filtrationmentioning
confidence: 99%
“…In addition, biomimetic and bioinspired solutions for separation technology and water filtration are topics of intense current interest (Goel et al, 2021;Bianciardi and Cascini, 2022;Hamann and Blanke, 2022;Zhang et al, 2022b). Recent discoveries of particle separation mechanisms in SF fishes have stimulated the development of biomimetic models with potential applications in microfluidics and commercial and industrial filtration for foods and beverages, wastewater, irrigation, oil spill remediation, and biotechnology products (e.g., Dou et al, 2017;Schroeder et al, 2019;Clark and San-Miguel, 2021;Adelmann et al, 2022;Masselter et al, 2023;Xu et al, 2023).…”
mentioning
confidence: 99%
“…Shiau et al [14] conducted technical prediction through scenario analysis. Masselter et al [15] applied scenario analysis to product failure analysis and found design problems by constructing product success scenario table.…”
Section: 2scenario Elementmentioning
confidence: 99%
“…These MP prevalence patterns do not appear to be reflected in the literature on interventions to control MP pollution, though. For example, there was a very limited focus on interventions designed to capture microfibers using laundry technologies [120] and microbeads [127] specifically. Targeted interventions such as these do not seem to be the norm since the size, ubiquity and indiscriminate release of MPs into freshwater environments would make such an approach unnecessary and/or ineffective in most instances [190].…”
Section: Types Of Mpmentioning
confidence: 99%